Research notes and communications: Characteristics distinguishing funded from unfunded business plans evaluated by venture capitalists - MacMillan, Ian C.; Narasimha, P. N. Subba (Strategic Management Journal, 1987)
Abstract Business plans that were funded by venture capitalists were compared to unfunded plans. Comparisons on the basis of plan structure, plan organization, and financial projections indicate that plans which deviate too far from the norm of the variables studied tend to go unfunded. Implications for plan preparation are discussed.